Usage of Scraped Data in Price Dynamic Measurement - Juszczak, Adam (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
Web‑scraping is a technique used to automatically extract data from websites. After the rise‑up of on‑lines shopping (which results in more shops posting their full price offer on their websites) it allows to acquire information about prices of goods sold by the retailers such as supermarkets or internet shops. Usage of web‑scraped data allows to lower the costs, improve the measurement quality and monitor the price change in real time. Due to before mentioned reasons this method became the object of research studies from both statistical offices (Eurostat, British Office of National Statistics, Belgium Statbel) and universities (for ex. Billion Prices Project conducted on MIT). However, usage of scrapped data for the CPI calculation entails with multiple challenges with their collection, processing and aggregation. The purpose of this article is to examine the possibility of using scrapped data in toy price dynamic analysis. Especially the purpose is to compare the results from different inde Xformulas. In this article the empirical study based on data from 4 different shops is presented (53 chosen products sold in Amazon, Wallmart, Smarterkids and KBKids).